An exploration of caregiver choice through the lens of Sartrean existentialism - Corey, Kristin L. (Nursing philosophy, 2017)
There are innumerable social and ethical factors which affect one's decision to become an informal caregiver for someone with chronic illness. The existential philosophy of Jean-Paul Sartre provides unique insight into human motivation and choice. The purpose of this paper was to examine the social and ethical influences on the individual's decision to become a caregiver through the lens of Sartrean existentialism and discuss how this unique philosophy can advance nursing knowledge. The factors affecting one's choice to become a caregiver were considered using the Sartrean existential concepts of The Other, human freedom, choice, bad faith, shame and authenticity. When explored through the perspective of Sartrean existentialism, the choice to become a caregiver is strongly influenced by fear of judgement from The Other and the resulting sense of social obligation and shame. However, the interaction with The Other often results in the loss of authenticity through the pursuit of bad faith. To avert bad faith, potential caregivers must act authentically by exercising their freedom to choose and by choosing an action for its own sake and not for some extraneous purpose. The results of this philosophical inquiry contribute to nursing knowledge by providing a unique, alternative perspective by which nurses may understand the choices of potential caregivers and support them in making authentic decisions. This perspective may provide a foundation for theory development and promote further nursing knowledge which will improve caregiver health and well-being.